Association of Healthcare Workers Characteristics with Exposure to any form of Violence at the Hospitals of Karachi - Jai Dev Maheshwari, Syeda Amber Zaidi, Kiran Khan, Nasima Iqbal, Syed Mohsin Turab, Ruqaya Nangrejo (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the prevalence and association of healthcare provider characteristics with exposure to any form of violence. To determine the frequency of change of workplace due to violence among medical doctors. Methods: The study was conducted at three Karachi government hospitals. Anyone who worked in outpatient, ward, or emergency department units of any age or gender was eligible to participate in the study. Surveys were conducted using a WHO-validated questionnaire, which included questions about exposure to violence and socio-demographic information. Results: Out of 300 people 52.7% were females and 47.3% were males. Chief Medical Officer /Medical Officers were twelve times more expected to be exposed to workplace violence than house officers. 26% of medical doctors had previously changed jobs. However, 19% of medical doctors had changed their workplace due to workplace violence. Conclusion: Violence of any kind was more common in doctors over the age of 35, and men were more vulnerable to violence. CMO/MO were more likely to engage in any form of violence than the rest of the profession. Last but not least, the frequency of medical doctors changing jobs due to violence was low.